2018
DOI: 10.1063/1.5008278
|View full text |Cite
|
Sign up to set email alerts
|

Growth and propagation of self-generated magnetic dipole vortices in collisionless shocks produced by interpenetrating plasmas

Abstract: Collisionless shocks generated by colliding relativistic plasmas are studied using particle-in-cell (PIC) simulations. The shock is produced due to the Weibel instabilities that generate current and density filaments and small-scale magnetic fields that are amplified from initial fluctuations. Localized regions of the strong magnetic field in the form of magnetic dipole vortices upstream of the shock are observed in the simulation developed during the nonlinear evolution of the electron and ion filaments. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…Electron vortex pairs are also observed in simulations of relativistic shocks, being responsible for electron energization in the upstream region (Naseri et al. 2018). Understanding the dynamics of vortex structures in plasmas is important for developing the theory of relativistic plasma turbulence (Bulanov et al.…”
Section: Introductionmentioning
confidence: 93%
“…Electron vortex pairs are also observed in simulations of relativistic shocks, being responsible for electron energization in the upstream region (Naseri et al. 2018). Understanding the dynamics of vortex structures in plasmas is important for developing the theory of relativistic plasma turbulence (Bulanov et al.…”
Section: Introductionmentioning
confidence: 93%
“…We studied the process of electron energization in interaction with MVs in the upstream of electron/ion shock using 2D PIC simulations. MVs are self-consistently generated in upstream of electron/ion collisionless shock 15 . The fields of MVs grow as they move toward shock region.…”
Section: Discussionmentioning
confidence: 99%
“…Counter stream electron flow are electrons that are either reflected off shock transition region, or escaped interaction with shock transition region. Recently we demonstrated that magnetic vortices (MVs) can self-consistently emerge in the upstream of electron/ion collisionless shocks with no external magnetic field 15 . The early stage of the interaction involves the generation of quasi-linear elongated MVs, which subsequently merge to form circularly shaped MVs (bubble).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of magnetic field based on ultra intense laser-plasma interactions has been investigated intensively in recent years [104][105][106] . Furthermore, the interactions of beam-plasma are also discussed for strong magnetic dipoles generation [107,108] . The magnetic field generation under the condition of ultra-intense laser interacting with underdense or near critical density plasma is discussed in this section.…”
Section: Static Magnetic Field Driven By Energetic Electron Beammentioning
confidence: 99%